NAVIGATING THE CHINA-RUSSIA ALLIANCE: A NEW PARADIGM IN INTERNATIONAL RELATIONS (Contemporary Journal of Social Science Review, 2025)
The China-Russia alliance signifies a transformative shift in the global power structure, shaping a new paradigm in international relations. Driven by mutual interests, this partnership is anchored in a shared opposition to Western dominance, particularly that of the United States and its allies. Strategic alignment is evident in defense cooperation, including joint military exercises, arms trade, and mutual support in regional conflicts. Economically, the partnership thrives through energy trade, infrastructure development, and integration with China's Belt and Road Initiative, offering Russia a vital economic lifeline amid Western sanctions. Politically, both nations leverage multilateral platforms such as BRICS and the Shanghai Cooperation Organization (SCO) to advocate for a multipolar world order and challenge Western-centric governance structures. This evolving alliance raises critical questions about its sustainability, as historical tensions and differing long-term objectives pose potential challenges. Nevertheless, the partnership’s growing influence on global issues—from Arctic exploration to technology collaboration—underscores its significance. By examining the strategic motivations, economic ties, and geopolitical implications of the China-Russia nexus, this study provides a nuanced understanding of how this alliance is reshaping global governance, security, and economic systems. The findings highlight the alliance's potential to redefine international power dynamics, challenging the established world order while offering opportunities for new forms of multilateral cooperation.